The influence of Pratylenchus penetrans on the incidence and severity of verticillium wilt of potato - Burpee, L L (Journal of nematology, 1978)
The influence of Pratylenchus penetrans on the incidence and severity of Verticillium wilt was examined in the potato cultivars 'Kennebec', 'Katahdin', and 'Abnaki'. Single-stem plants were grown in soil maintained at a temperature of 22 +/- 1 C. Axenically cultured nematodes were suspended in water and introduced to the soil, at a rate of ca 5,000/25.4-cm pot, through holes made around each stem. Ten days after infestation with nematodes, conidial suspensions of Verticillium albo-atrum were introduced into the soil at a rate of ca 1,000,000/pot. Among Katahdin plants, the severity of foliar symptoms was increased in the presence of both pathogens 2 and 3 weeks after soil intestation. During the remaining 5 weeks, severity of foliar symptoms was not different between plants infected by both pathogens and those infected by Verticillium alone. Within the wilt-susceptible cultivar Kennebec and the resistant eultivar Abnaki, no effects on foliar symptom severity were observed. When plant heights, shoot weights, and tuber yields were analyzed, a Pratylenchus-Verticillium interaction was not evident within any of the cultivars tested. Nematode populations in roots and rhizosphere were suppressed in Kennebec and Katahdin plants in the presence of Verticillium